Palen, Marc-William. Pax Economica: Left-Wing Visions of a Free Trade World - Jha, Saumitra (Journal of Economic Literature, 2025)
Saumitra Jha of Stanford University reviews “Pax Economica: Left-Wing Visions of a Free Trade World” by Marc-William Palen. The Econlit abstract of this book begins: “Examines the anti-imperialist dissent that accompanied the global spread of imperialism, focusing in particular on how free-trade cosmopolitanism facilitated the international peace and anti-imperialist movements that occurred from the mid-nineteenth century to the present.”